Hubungan Dukungan Emosional Bidan terhadap Tingkat Kecemasan Ibu Primigravida dalam Proses Kala I di RSU Imelda Pekerja Indonesia Medan Tahun 2023 - Risa Tantry Gultom; Yohana Simbolon; Hotmauli Sitanggang (Jurnal Anestesi, 2024)
Introduction: Primigravida pregnant women are women who are pregnant for the first time. This first pregnancy causes discomfort during pregnancy that the pregnant mother can feel. Objective: to determine the relationship between midwives' emotional support and the level of anxiety of primigravida mothers in the 1st stage of the process at Imelda Hospital in Medan. Materials and Methods: This research uses quantitative methods with bivariate test analysis and discrete statistics. Results: This study aims to determine the relationship between midwives' emotional support and the level of anxiety of primigravida mothers during the 1st stage. The total research sample was 40 respondents. The results of the analysis of the relationship between midwives' emotional support and the level of anxiety of primigravida mothers. 23 people (23%) did not receive support from midwives. The majority of the anxiety levels faced by pregnant women during the first stage of the process were moderately anxious, 22 people (55%). Conclusion: The characteristics of pregnant women respondents at RSU IPI showed that 28 people aged 21-30 years (70%) had high school education (28 people) (70%) did not receive support from a midwife as many as 23 people (23%) The level of anxiety faced by pregnant women During the first stage of the process, the majority had moderate anxiety, 22 people (55%). Emotional support and the level of anxiety showed that the majority who did not receive support experienced severe anxiety, namely 15 people. Those who received support only experienced moderate anxiety, 14 people.